A Filter Paper‐Based Nanogenerator via Water‐Drop Flow. (31st May 2019) - Lu, Yuanchao; Wu, Hui; Yang, Qunqing; Ping, Jianfeng; Wu, Jian; Liu, Jun
Abstract: With the increase in energy crisis, it is a promising strategy to develop a nanogenerators for harvesting small amounts of energy. Herein, a flexible and robust filter paper‐based nanogenerator (FPNG), fabricated by printing a modified multiwalled carbon nanotubes ink slurry on filter papers with the specific as‐designed shape, is developed. The results show that the streaming voltage and current are induced from the water‐drop flow across the surface of FPNG, such as rainwater. Compared with the energy‐harvesting performance of FPNG under different conditions, the maximum streaming voltage is obtained with 20 mL h −1 injection speed of 1 × 10 −3 m NaCl solution at 75° placement angle for quantitative medium speed FPNG. Under optimum conditions, the power reaches to 9.91 ± 1.39 pW per droplet. Then, the streaming voltage and current produced from dropping rainwater onto the FPNG are investigated and the power is 2.4 ± 0.65 pW per droplet. It is assumed that there are abundant pores and oxygen‐containing functional groups on the surface of filter papers with overlapped and crosslinked morphology, providing vast active sites and ion diffusion channels to enhance the electric double layer capacitance. Therefore, FPNG has good prospects for applications in harvesting energy from water‐drops. Abstract : In this paper, a filter paper‐based nanogenerator (FPNG) is developed. The streaming voltage and current are induced from the water‐drop flow across over the surface of the FPNG. Under optimum conditions, the power of the FPNG reaches to 9.91 ± 1.39 pW per droplet. FPNG is an efficient strategy to collect energy from water‐drops.